Constructing and contesting threat: Representations of white British Muslims across British national and Muslim newspapers. (19th February 2018) - Amer, Amena; Howarth, Caroline
Abstract: White British Muslims pose a challenge to racialised representations of British Muslims as non‐white, foreign and Other. By drawing on tools from Critical Discourse Analysis to develop Social Representations Theory on a micro‐analytic level, and making connections with other relevant social psychological theories on intergroup relations, this article examines the constructions of white British Muslims as a threat in six national and two Muslim British newspapers. It looks at how discourses are used to create, perpetuate and challenge the 'hegemonisation' of social representations in majority and minority press. The findings show that white British Muslims are portrayed as a threat not just despite of, but because of, their position as part of the 'white British' ingroup. Consequently, the threat they pose often leads to their Muslimness being emphasised. This was, at times, contested, however, either through direct challenges, or by making the threat ambivalent by drawing on their whiteness.